“Loving Our Own Bones”: Intimate and Life Affirming Work - Young, Thelathia Nikki (Journal of disability & religion, 2024)
Julia Watts-Belser offers readers a gift in her outstanding book. She invites us to notice a liberative and life-giving epistemological frame, one that calls us all into being with ourselves that does not dismiss our bodies and selves but that beckons us towards attention and appreciation, honest looking, and compassionate care of who we really are, how we are diversely and variably made, and how we make our way in this world. This brief essay features two questions: What does it mean to know through a lens of subversive knowledge? And. How ought we read and investigate new possibilities (of knowing) that emerge from disability wisdom?